Programmable Direct Memory Access Controller Design Using Advanced High Performance Bus Protocol (International Journal of Engineering and Computer Science, 2018)
Direct memory access is process, which allows certain peripheral devices to access system memory without intervention of CPU. When CPU is performing I/O operation, it will occupy the entire duration of IOR/IOW operations and hence it is unavailable to do other operations. The DMAC is mainly helps in efficient utilization of hardware resources.